Community Participation in the Management and Maintenance of Urban Drainage Systems in Sungai Penuh City as a Flood Mitigation Effort: A Case Study of Jl. M.H. Thamrin (Simpang Tiga Rawang Village, Hamparan Rawang District) - Sari, Inda Puspita; Khadavi, Khadavi; Mizwar, Zuherna (Jurnal Talenta Sipil, 2025)
Flooding is a natural phenomenon that frequently occurs in Indonesia, especially during the rainy season. In Sungai Penuh City, drainage blockage due to poor maintenance is also one of the causes of flooding. Drainage systems are often not well-maintained due to the government's budget constraints. Community participation in drainage maintenance activities is expected to serve as an alternative solution to minimize flood risks. Therefore, this study was conducted to examine the drainage management and maintenance system, the level of community participation in drainage maintenance activities, and recommended solutions to optimize community involvement in drainage maintenance. The study was conducted on JL. M. H. Thamrin, Simpang Tiga Rawang Village. The assessment indicators for community participation levels were based on the Indonesian Ministry of Public Works Regulation No. 12/Prt/M/2014 concerning the Implementation of Urban Drainage Systems. This research employed a combination of quantitative and qualitative methods. The qualitative method involved interviews with informants, while the quantitative method utilized a Likert-scale questionnaire assessment for 90 households. The results indicate that out of six assessment indicators, four show that community participation in drainage maintenance remains low (below 40%). However, two indicators demonstrate active community participation, namely the prevention of building construction over drainage channels (76.67%) and reporting information to the government (57.70%). The recommended alternative solutions to enhance community participation include increasing public education through socialization, enforcing regulations and sanctions, and encouraging local communities to actively mobilize residents in self-sustained drainage maintenance efforts.